Positioning Pathways Provision Within Global and National Contexts - Brett, Matt; Pitman, Tim (Springer, 2018)
This chapter positions the increase in the provision of pathway programs, including foundation and enabling programs, as a function of global trends shaping higher education and localised responses to social, economic, political and cultural factors. These localised responses play out against a broader global context, in which the increasing mobility of students looms large. Demography, politics, history and economics all contribute to considerable diversity in the structure, financing and market composition of higher education systems. In turn, these factors shape the purpose, design and delivery of pathway programs. This chapter draws upon UNESCO, OECD and World Bank data sets to contextualise relevant examples of African, Australasian, European, Middle East, and North American higher education systems, against each other and other international benchmarks. The trajectory of these education systems across time demonstrates convergence towards higher levels of school participation and massification of higher education participation, but also differential patterns of international student mobility and responsiveness to national contextual factors. The signs are that global forces and national context will continue to shape the evolution of pathway programs internationally.